Prescription Factors Associated with Medication Non-adherence in Japan Assessed from Leftover Drugs in the SETSUYAKU-BAG Campaign: Focus on Oral Antidiabetic Drugs - Koyanagi, Kaori; Kubota, Toshio; Kobayashi, Daisuke; Kihara, Taro; Yoshida, Takeo; Miisho, Takamasa; Miura, Tomoko; Sakamoto, Yoshiko; Takaki, Junichi; Seo, Takashi; Shimazoe, Takao (Frontiers in Pharmacology, 2016)
Background: Medication adherence has an important influence on health outcomes in patients with chronic diseases. However, few studies have been performed in Japan to determine factors related to medication non-adherence. Objective: The aim of this study was to identify prescription factors related to medication non-adherence by investigating patient characteristics, all prescriptions, and prescriptions for oral antidiabetic drugs (OADs). Methods: A retrospective cross-sectional survey of prescription data about implementation of dosing regimen was performed at community pharmacies engaged in appropriate use of leftover drugs. We evaluated the amount of drugs originally prescribed and the reduced amount after use of leftover drugs, and then calculated prescription reduction ratio (PRR). We analyzed prescription factors contributing to non-adherence based on the PRR. Results: Prescription information for 1,207 patients was reviewed, revealing that patients were non-adherent to 58% of prescriptions. Lack of a drug copayment, fewer concurrent drugs, and drugs not in single-dose packaging were associated with non-adherence. Among the 1,207 patients, 234 prescriptions for diabetes and 452 OAD formulations were included. Forty-seven percent of prescriptions and 29% of the formulations were non-adherent. A higher dosing frequency and preprandial administration were associated with non-adherence. Among the OADs, adherence was lower for α-glucosidase inhibitors and biguanides than for sulfonylureas. Conclusions: Several factors related to patient characteristics, general drug prescriptions, and OAD prescriptions were associated with non-adherence. Further consideration will be needed to improve adherence to medication in Japan. Health care providers should perform more careful monitoring of adherence in patients with the factors identified by this study.